Chromosomal abnormalities in patients with oligozoospermia and non-obstructive azoospermia - Pylyp, Larysa Y. (Springer US, 2013)
PURPOSE: To assess the frequency and types of chromosomal abnormalities in 204 Ukrainian patients with non-obstructive azoospermia and oligozoospermia and 87 men with normozoospermia. METHODS: Cytogenetic studies were performed on peripheral blood lymphocyte samples of 164 men with oligozoospermia, 40 men with non-obstructive azoospermia and 87 men with normozoospermia attending infertility clinic. RESULTS: Chromosomal abnormalities were detected in 17 % of patients with sperm disorders: in 35 % of men with azoospermia and in 12.7 % of men with oligozoospermia. The frequency of chromosomal abnormalities in patients with sperm disorders was significantly higher, than in patients with normozoospermia (P = 0.0001). An increase in the incidence of chromosomal abnormalities with the decrease of sperm count was observed. Chromosomal abnormalities were detected in 1.1 % of patients with normozoospermia, 6.5 % of patients with mild oligozoospermia (sperm count 5–15 × 10(6)/ml), 18.4 % of patients with severe oligozoospermia (sperm count <5 × 10(6)/ml) and 35 % of patients with azoospermia. A significant increase in the frequency of chromosomal abnormalities in patients with severe oligozoospermia was observed when compared to mild oligozoospermia (P = 0.01). A statistically significant association (P = 0.02) of chromosomal abnormalities and sex chromosome abnormalities (P = 0.0001) with azoospermia when compared to oligozoospermia was observed. CONCLUSIONS: Our results highlight the importance of cytogenetic studies in patients with oligozoospermia (both mild and severe) and non-obstructive azoospermia. The presence of chromosomal abnormalities influences significantly the fertility treatment protocols, as well as provides a definite diagnosis to couples suffering from infertility.